2022
DOI: 10.1088/1674-1056/ac3067
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing the photo-luminescence stability of CH3NH3PbI3 film with ionic liquids

Abstract: The methylammonium lead triiodide (CH3NH3PbI3)-based perovskite shows a great alluring prospect in areas of solar cells, lasers, photodetectors, and light emitting diodes owing to their excellent optical and electrical advantages. However, it is very sensitive to the surrounding oxygen and moisture, which limits its development seriously. It is urgent to spare no effort to enhance its optical and electrical stability for further application. In this paper, we synthesize the MAPbI3 perovskite film on the glass … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…There is still a way to go for the practical applications, and methods needs to be used to further strengthen the long-term stability, such as the construction of core-shell structure, ion doping, etc. [55][56][57][58]…”
Section: Resultsmentioning
confidence: 99%
“…There is still a way to go for the practical applications, and methods needs to be used to further strengthen the long-term stability, such as the construction of core-shell structure, ion doping, etc. [55][56][57][58]…”
Section: Resultsmentioning
confidence: 99%
“…In light of this study, Ma et al incorporated BMIMBF 4 into the perovskite precursor solution as an additive for perovskite materials. [ 65 ] After BMIMBF 4 passivation, the surface of the perovskite film is more uniform and smoother, and the density of grain boundaries became less than that of the film before passivation, which was due to the fact that the ILs in the film promote the growth of grains. It was further discovered that the utilization of BMIMBF 4 led to an enhancement in the chemical stability of the perovskite lattice by effectively occupying the vacant ion (I − or MA + ) sites and fixing the ions through the interaction between ions to prevent the carrier migration from the perovskite lattice, thus improving the carrier recombination rate of the perovskite layer.…”
Section: Additive Engineering In Pscsmentioning
confidence: 99%
“…To promote the commercialization of OIHP solar cell, the profound understanding of the light-induced degradation mechanism is necessary. [20,[79][80][81] The light-induced degradation mechanism of conventional 3D perovskites is a complex dynamic process, accompanied by the photo-generated superoxide O − 2 to promote the deprotonation of methyl-ammonium as well as the migration of the halide ions. Recently, Anaya et al clearly revealed that the electrostatic repulsion of the superoxide O − 2 negatively charge layer on the surface of OIHP created under illumination provides a driving force for halide ions to migrate toward bulk from illuminated areas, and the reaction between O − 2 anions and perovskite causes further degradation by formation of volatile methylamine.…”
Section: Light Stabilitymentioning
confidence: 99%